Immunoadjuvant activity of amphotericin B as displayed in mice infected with Candida albicans. - Bistoni, F (1985)
Mice receiving a single intraperitoneal injection of amphotericin B showed increased resistance to subsequent challenge with either Candida albicans or Staphylococcus aureus. This enhancement of resistance was obvious in terms of both survival criteria and clearance of the intravenously injected organism from different organs. The protective effect of amphotericin B was conditioned by dose, time of drug administration, and size of yeast or bacterial inoculum and was reversed by cyclophosphamide. Effector cells from mice treated with amphotericin B displayed enhanced fungicidal activity in vitro as measured in a short-term 51Cr release assay. Macrophages from intact animals exposed in vitro to amphotericin B also acquired strong candidacidal reactivity.